Surgery to the primary tumor is associated with improved survival of patients with metastatic esophageal cancer: propensity score-matched analyses of a large retrospective cohort. Issue 3 (7th June 2019) - Zhang, Rui; Zou, Jiahua; Li, Ping; Li, Qin; Qiao, Yunfeng; Han, Jianglong; Huang, Kejie; Ruan, Peng; Lin, Huiqing; Song, Qibin; Fu, Zhenming
SUMMARY: The survival advantage of surgery to the primary tumor for patients with distant metastatic esophageal cancer has not been adequately evaluated. This study aims to investigate the role of surgery to the primary tumor in distant metastatic esophageal cancer and to evaluate possible different effects of surgery on survival of esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC). This study included a cohort of 4, 367 metastatic esophageal cancer patients from the Surveillance, Epidemiology, and End Results (SEER) database, registered from January 2004 to December 2014. Kaplan-Meier and Cox proportional hazardous models were used to evaluate the overall survival (OS) and corresponding 95% confidence interval (CI). Propensity score matching (PSM) was used to adjust for potential baseline confounding. Both EAC (median OS for surgery group vs. no-surgery group–14.0 vs. 9.0 months, P < 0.001) and ESCC (median OS for surgery vs. no-surgery group–11.0 vs. 7.0 months, P = 0.002) experienced survival benefits from surgery. We found that surgery to the primary tumor, when combined with chemotherapy, was associated with improved survival for patients with M1b disease, both EAC and ESCC, with a greater benefit observed in younger patients, and those with EAC. While the present data indicate a potential survival benefit from surgery for some patients with metastatic esophageal cancer, it is possible that performance status and metastatic disease burden impacted patient selection, influencing these results. Further studies are needed to determine the role of surgery for patients with metastatic esophageal cancer.